SYPHILIS: : THE IMAGETIC NARRATIVE OF THOSE (CON)LIVE IN THE MUNICIPALITY OF BRAGANÇA-PA, BRAZILIAN AMAZON COAST (Interdisciplinary Studies Journal, 2024)
The research addresses syphilis in the context of the Bragantina region, northeast of the state of Pará, Brazilian Amazon, an infection that has challenged humanity for centuries, considered worldwide the second most serious sexually transmitted infection, after that caused by the Human Immunodeficiency Virus (HIV) , which can affect the entire family, as it is transmitted from mother to child during pregnancy. It is preventable, easy to identify and has a cure. In the Amazon Region of Bragança, a municipality in the State of Pará, there are public health actions to attempt to control this infection. By narrating the oral history of a teenager infected with syphilis, who transmitted the bacteria to her son, during the dialogue in a hospital environment with the health professional (researcher) in May 2023, the aim is to provoke an analysis of agencies that affect the vulnerable being living in this territory, faced with symbolic clashes between curative and traditional medicine in a situation of fragile health fraught with stereotypes and marginalization of the affected person. Methodologically, the study took place through a bibliographic review and case study followed in May 2023 in a public hospital in Bragança-PA. The main results point to the importance of the narrative of an Amazonian woman doubly weakened, due to the postpartum period and the involvement of her baby at such an early period of life, allowing intercultural discussion to move between knowledge in order to raise reflections on improvements in care and attention given by those who experience unique stories in this Amazonian space.
Keywords: Adolescent; Woman; Oral History; Amazon